2020
DOI: 10.4067/s0717-95022020000100017
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Artery Tortuosity Index on Abdominal CT Scan: Correlation with Age, Sex, BMI and Abdominal Cavity Diameters

Abstract: Thorough knowledge of splenic artery course and morphology may help clinician to provide better practice. This Study aims at finding out if there was a relationship between splenic artery tortuosity index and age, sex, Body Mass Index (BMI) and abdominal cavity diameters. Routine abdominal Computerized Tomography (CT) scan images were retrospectively analyzed for 219 patients. Splenic artery tortuosity index was calculated. Abdominal cavity diameters were measured. Age, sex, and BMI were recorded. Splenic arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The splenic artery (SA) is described as the first branch of CT (2.5%) 7 , but these morphological features were not observed in our study. The length of the SA was 92.5 mm, while in other studies the range fluctuates from 76.5 to 94.1mm 1,27 . Concerning the tortuosity of the SA, the results from Fataftah et al 2020 27 report 94.1mm for the straight SA, and 155 mm for the tortuous SA, with a tortuosity index (TI) of 1.63, higher than our TI of 1.25.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The splenic artery (SA) is described as the first branch of CT (2.5%) 7 , but these morphological features were not observed in our study. The length of the SA was 92.5 mm, while in other studies the range fluctuates from 76.5 to 94.1mm 1,27 . Concerning the tortuosity of the SA, the results from Fataftah et al 2020 27 report 94.1mm for the straight SA, and 155 mm for the tortuous SA, with a tortuosity index (TI) of 1.63, higher than our TI of 1.25.…”
Section: Discussionmentioning
confidence: 71%
“…The length of the SA was 92.5 mm, while in other studies the range fluctuates from 76.5 to 94.1mm 1,27 . Concerning the tortuosity of the SA, the results from Fataftah et al 2020 27 report 94.1mm for the straight SA, and 155 mm for the tortuous SA, with a tortuosity index (TI) of 1.63, higher than our TI of 1.25. Silvester et al 19 found, in cadavers and using angiography imaging, a TI range for cadavers of 1.01-3.58, and higher in the imaging analysis (5.25 TI), with no correlation between the TI of the SA and female gender, body mass index, abdominal cavity diameter, nor age.…”
Section: Discussionmentioning
confidence: 71%
“…However, one of the studies of the tortuosity of the splenic artery did not reveal a relationship with age or body weight, but instead indicated a relationship between the female sex and a high degree of tortuosity. The authors suggested that this is due to the peculiarity of the influence of female sex hormones on the walls of blood vessels [ 15 ]. However, Brinkman and coworkers did not find any relationship between splenic artery loops and age or sex but determined that the length of the artery in contact with the pancreas decreased with age [ 12 ].…”
Section: Discussionmentioning
confidence: 99%